Boosting Energy Transfer from Self‐Trapped Exciton to Er3+ Through Sb3+ Doping in Cs2Na(Lu/Er)Cl6 Double Perovskites. Issue 3 (13th December 2022) - Zhang, Guodong; Dang, Peipei; Tian, Long; Yang, Wei; Cheng, Ziyong; Lian, Hongzhou; Lin, Jun
Abstract: Metal halide double perovskites are highly attractive for optoelectronic applications because of their superior optical properties. Here, a novel halide double perovskite, Cs2 NaLuCl6, exhibiting bright blue emission originating from the host self‐trapped exciton (STE) is reported. Through doping with Sb 3+, the dopant‐induced STE is formed in the crystals with a photoluminescence quantum yield up to 94%. The energy transfer from the dopant STE to Er 3+ is superior to the direct excitation of Er 3+, which is more efficient than the energy transfer from the host STE to Er 3+ . Furthermore, the energy transfer efficiency from STE to Er 3+ is boosted from 8% to 33% through Sb 3+ doping in Cs2 NaLu0.95 Er0.05 Cl6 . Due to the strong electron‐phonon coupling and efficient energy transfer, the as‐prepared crystals exhibit intense dual‐band emissions and remarkable thermal stability. Importantly, the STE emission variation after the Er 3+ ‐substitution is explored based on the electron‐phonon coupling effect. These findings provide new insights into the excited state dynamics of halide double perovskites and extend their luminescence applications such as white light‐emitting diodes and night vision. Abstract : A new class of double perovskites of Cs2 NaLuCl6 with blue host self‐trapped exciton (STE) emission is reported. The tunable blue‐to‐green emission with a photoluminescence quantum yield up to 94% is achieved by introducing Sb 3+ and Er 3+ . Compared with the energy transfer from the host STE to Er 3+, the energy transfer from the dopant STE to Er 3+ is more efficient than the direct excitation of Er 3+, which can overcome the weak absorption cross‐section of f–f transition from Er 3+ .